Correlation between uniaxial compressive strength and point-load index strength - Sundara, Parameswary (2009)
In verifying the material properties of rock, laboratory test need to be carried out to ensure a safe design of structures. Among the most common rock properties verified in laboratory are uniaxial compressive strength test (UCS) and point-load index strength test (Is50). These two rock properties are often correlated for ease of evaluating rock properties particularly during preliminary design stage. The focus of this study is to verify correlation factor between UCS and Is(50) and to compare with established correlation. Rock types investigated are granite collected from Tumpat, Kelantan and limestone from Pandan Indah, Kuala Lumpur. The samples of granite and limestone are in fresh state (grade 1). Literature review shows that the conversion factor, K for correlating between UCS and Is(50) lies between 16-29. From this study, verification of laboratory test data shows that there is no clearly good correlation between UCS and Is(50). Variation on test data has been observed. This is expected for natural material like rock. The insignificance relationship of strength signifies that there is possibility of insufficient data of rock samples. Although there are some trends that correlate UCS and Is50 for the rock types investigated, however due to significant variation of data and limited number of samples tested, the correlation obtained is not clearly present good linear relationship between the two properties. To improve this more samples should be verified for both properties.